An interdisciplinary study of the effect of laser radiation on carbon fiber-reinforced polymer, in the context of counteracting unmanned aerial vehicles - Oleksandr Siora; Volodymyr Lukashenko; Artemii Bernatskyi (Історія науки і техніки, 2025)
This article presents an interdisciplinary study that combines historical analysis and experimental research to explore the vulnerability of military drones made from carbon fiber-reinforced polymer to destruction by laser radiation. The work is structured around two interconnected areas: the historical evolution of carbon fiber-reinforced polymer use in military drone construction and the parallel development of high-energy laser systems as precision countermeasures. The historical section traces the trajectory of carbon fiber composites from their initial applications in aerospace and defense industries during the late 20th century to their widespread adoption in military unmanned aerial vehicles, driven by the need for lightweight, durable, and radar-evading materials. Special attention is given to geopolitical, technological, and strategic factors that influenced the increasing reliance on carbon fiber-reinforced polymer for enhancing drone performance in terms of range, payload, and survivability. In parallel, the article examines the emergence of directed energy weapons, focusing on laser systems, as a response to the limitations of conventional kinetic countermeasures in neutralizing fast, small, and low-observable drones. The study outlines how the military’s growing concern with swarm attacks and stealth unmanned aerial vehicles has accelerated investments in laser-based air defense systems capable of engaging airborne targets with high accuracy and low operational cost. The experimental component investigates the mechanisms of laser-induced damage in carbon fiber-reinforced polymer materials through controlled laboratory tests, during which samples are exposed to varying intensities and durations of laser radiation. The results are analyzed to determine the energy thresholds and exposure conditions that lead to effective material destruction. By synthesizing historical and experimental data, the article provides a comprehensive understanding of how past material choices have shaped current vulnerabilities in drone technology and how modern laser systems are specifically adapted to exploit those weaknesses. This integrated approach not only bridges the gap between history and applied science but also contributes to the development of more effective and informed counter-drone strategies in contemporary and future military operations.